Treatment efficacy of low-dose 5-fluorouracil with ultrasound in mediating 5-fluorouracil-loaded microbubble cavitation in head and neck cancer - Ai-Ho Liao; Yu-An Lee; Dao-Lung Lin; Ho-Chiao Chuang; Jehng-Kang Wang; Ching-En Chang; Hsiang-Tzu Li; Ting-Yi Wu; Cheng-Ping Shih; Chih-Hung Wang; Yueng-Hsiang Chu (Taylor & Francis Group, 2023)
AbstractOver the past 50 years, 5-fluorouracil (5-FU) has played a critical role in the systemic chemotherapy of cancer patients. Bolus intravenous (IV) 5-FU infusion has been used due to the limitation of its extremely short half-life (10-15 min). This study used ultrasound (US) mediating 5-FU-loaded microbubbles (MBs) cavitation as a tool to increase local intratumoral 5-FU levels with a reduced dose of 5-FU (a single IV injection of 2.5 mg/kg instead of a single intraperitoneal injection of 25-200 mg/kg as used in previous studies in mice). The 5-FU-MBs were prepared with a 132 mg/mL albumin solution and a 0.30 mg/mL 5-FU solution. The diameters of the MBs and 5-FU-MBs were 1.24 ± 0.85 and 2.00 ± 0.53 µm (mean ± SEM), respectively, and the maximum loading efficiency of 5-FU on MBs was 19.04 ± 0.25%. In the in vitro study, the cell viabilities of 5-FU and 5-FU-MBs did not differ significantly, but compared with the 5-FU-MBs treatment-alone group, cell toxicity increased to 31% in the 5-FU-MBs + US group (p < 0.001). The biodistribution results indicated that the 5-FU levels of the tumors in small animals were significant higher for the 5-FU-MBs + US treatment than for either the 5-FU-MBs or 5-FU treatment with low 5-FU systemic treatment doses (2.5 mg/kg 5-FU IV). In small-animal treatment, 2.5 mg/kg 5-FU therapeutic IV doses injected into mice caused a more-significant reduction in tumor growth in the 5-FU-MBs + US group (65.9%) than in the control group after 34 days of treatment.